ChemInform Abstract: Consecutive Tandem Cycloaddition Between Nitriles and Azides: Synthesis of 5‐Amino‐1H‐[1, 2, 3]‐triazoles. Issue 18 (11th April 2013) - Gomes, Ana T. P. C.; Martins, Priscila R. C.; Rocha, David R.; Neves, Maria G. P. M. S.; Ferreira, Vitor F.; Silva, Artur M. S.; Cavaleiro, Jose A. S.; da Silva, Fernando de C.
Abstract With equimolar amounts of nitrile, the title reaction gives aminotriazoles.